Comprehensive genomic profiling of upper tract urothelial carcinoma and urothelial carcinoma of the bladder identifies distinct molecular characterizations with potential implications for targeted therapy & immunotherapy - Tang, Qi; Zuo, Wei; Wan, Chong; Xiong, Shengwei; Xu, Chunru; Yuan, Changwei; Sun, Qiangqiang; Zhou, Liqun; Li, Xuesong (Frontiers in Immunology, 2023)
Backgrounds: Despite the genomic landscape of urothelial carcinomas (UC) patients, especially those with UC of bladder (UCB), has been comprehensively delineated and associated with pathogenetic mechanisms and treatment preferences, the genomic characterization of upper tract UC (UTUC) has yet to be fully elucidated. Materials and Methods: A total of 131 Chinese UTUC (74 renal pelvis & 57 ureter) and 118 UCB patients were enrolled in the present study, and targeted next-generation sequencing (NGS) of 618 cancer-associated genes were conducted to exhibit the profile of somatic and germline alterations. The COSMIC database, including 30 mutational signatures, were downloaded to evaluate the mutational spectrums. Moreover, TCGA-UCB, MSKCC-UCB, and MSKCC-UTUC datasets were retrieved for preforming genomic alterations (GA) comparison analysis between Western and Chinese UC patients. Results: In our cohort, 93.98% and 56.63% of UC patients were identified with oncogenic and actionable somatic alterations, respectively. Besides, 11.24% of Chinese UC patients, including 14.50% and 7.63% of UTUC and UCB cases, respectively, harbored a total of 32 pathogenic/likely-pathogenic germline variants in 22 genes, with the highest prevalence in BRCA1 (1.20%) and CHEK2 (1.20%). In addition, Chinese UTUC and UCB patients possessed distinct features in somatic GAs, especially in KMT2D/C/A, GNAQ, ERCC2, RB1, and PPM1D. Meanwhile, we found notable differences in the prevalence of ELF3, TP53, PMS2, and FAT4 between renal pelvis and ureter cancers. Notably, 22.90% and 33.90% of UTUC and UCB patients, respectively, had at least one deleterious/likely deleterious alteration in DNA damage repair (DDR) related pathways. Regarding COSMIC database analysis, patients with mutational signature 22 consistently had the markedly higher level of tumor mutational burden (TMB), irrespective of UTUC or UCB. By comparison, Chinese and Western UTUC patients differed regrading GAs in key genes and oncogenic pathways, especially in TP53 pathway, RTK/RAS and PI3K pathways; meanwhile, more alterations in WNT pathway but less TP53, RTK/RAS, HIPPO, and PI3K pathways were identified in Chinese UCB. Conclusions: The in-depth analysis of genomic mutational landscapes revealed distinct pathogenetic mechanisms between Chinese UTUC and UCB, and specific genomic characterizations could identify high risk population of UTUC/UCB and provided information regarding the selection of alternative therapeutic regimens.